ANALYSIS OF THE DEVELOPMENT OF ENVIRONMENTAL CHARACTER THROUGH THE REDUCE, REUSE, RECYCLE (3R) PROGRAM - Wiwid Sekar Utami; Desy Safitri; Sujarwo (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Character development is an effort that is sustainable on the foundation of character education that has been carried out, the form of character development varies, it is in accordance with the eighteen values of character education in Indonesia, and the focus of this research is the character of environmental love. The character of environmental love carried out at SMPN 45 Jakarta can be developed through one program among other programs, namely through Reduce, Reuse, Recycle activities. The purpose of this study is to further describe 3R activities can develop the character of environmental love of SMPN 45 Jakarta students. The research method used in this research is descriptive quantitative, and the final results of this study indicate that the development of environmental love character carried out by SMPN 45 Jakarta is well implemented, this is supported because of the dominance of reinforcement by teachers, and rules at school. but it is unfortunate that the environmental love behavior implemented by students is only limited to compulsion, not fully aware of environmental sustainability and running wholeheartedly.